Curaçao: Smart Nation - From Smart city to Sage society - Goede, Miguel (Archives of Business Research, 2018)
Purpose – The purpose of this article is to describe the case of Curaçao striving to become a smart nation. Many in Curaçao talk about Smart Nation, Smart Island and the blue economy. In practice not much is noted, till now. Why? Methodology – For this study, a literature review was conducted and interviews were held with key figures. Several webinars were conducted and a conference was attended. The draft version of this article was discussed with key persons. Findings – In general Curaçao is not good at implementing policies. Some of the causes include the fragmentation of the society as well as its leadership; as a consequence of patronage and nepotism, incompetent managers and professionals are appointed in key positions. For Curaçao to become a smart island the mindset of the people must shift. Originality – The paper contributes to the understanding of obstacles in the development of small island states.